Unlocking Urban Breathability: Investigating the Synergistic Mitigation of PM2.5 and CO2 by Community Park Green Space in the Built Environment Using Simulation - Xina Ma; Mengyao Wang; Xiaoling She; Jingyuan Zhao (Buildings)
Reducing carbon emissions and controlling air pollution is a dual challenge for China in addressing climate change. Analyzing the synergistic relationship between PM2.5 and CO2 in urban green spaces has become an important part of promoting pollution control. The study investigated the influence and synergistic relationship between the spatial pattern of community parks on PM2.5 and CO2 in Xi’an City, Shaanxi Province, through practical measurement and ENVI-met/Open Studio simulation calculations. The results showed that: (1) Within the sphere of influence, community parks exhibit a positive synergy varying with distance, peaking at 400 m and declining as 300 m > 500 m > 200 m > 100 m. (2) The green space rate, total edge (TE), and mean patch shape index (SHAPE_MN) positively influence the synergistic mitigation of PM2.5 and CO2, with a defined maximum impact boundary. The strongest synergistic reduction of PM2.5 and CO2 occurs at a green space rate of 85%, TE1200, and SHAPE1.2, with optimal influence boundaries of 300 m, 200 m, and 100 m, respectively. This conclusion demonstrates the key role of green space in community parks in the synergistic abatement and provides a scientific basis and practical guidance for the planning and design of urban green space under the goal of “dual-carbon”.